PEMBERDAYAAN PASIEN DIABETES MELITUS DALAM PERAWATAN KAKI BERBASIS M-DFEET APPLICATION DAN VIDEO PERAWATAN KAKI DI WILAYAH PUSKESMAS DENPASAR SELATAN - Agustini, Ni Putu Inca Buntari; Suyasa, I Gede Putu Darma; Megayanti, Sri Dewi; Sari, Ni Made Candra Citra; Dewi, Ni Putu Ayu Ratna; Putra, I Komang Ardidhana Nugraha; Wardana, Dewa Gede Wisnu; Wijayantha, I Putu Arya (Community Development in Health Journal, 2024)
Introduction & Aim: The diabetic foot problem is potentially the most preventable long-term complication of diabetes. Programs and instruments related to the early detection of diabetic feet, especially in Indonesia, are still experiencing problems because they have not yet implemented an information technology approach. Novel discoveries that are inventive, imaginative, efficient, and simple for patients to do on their own are needed for these illnesses. A mobile application known as Mobile Diabetic Foot Early Self-Assessment (M-DFEET) was created for Android. The purpose of community service was to empower families and DM patients to independently perform foot examinations and care using the M-DFEET application and audio-visual media. Method of Activity: The steps of this community service activity follow the POAC concept approach: planning by assessing community service activities with partners, organizing via approaches with relevant parties, and determining if DM patients are prepared to receive instruction. Actuating and Controlling conducted training for DM patients regarding independent foot care with the M-DFEET application and audio-visual media, evaluation, and reflection, which were carried out three times (June until August 2023). Results: the average value of the knowledge level of the respondents before training on foot care with M-DFEET and audiovisual media was 9.07 and increased to 12.37 after the training. The attitude of respondents before training on foot care with M-DFEET and audiovisual media had an average of 49.37 and increased to 61.37 after being given training. Respondents' skills before being given foot care training with M-DFEET and audiovisual media had an average of 9.90 and increased to 13.03 after being given training. Discussion: There is an effect of foot care training with M-DFEET and audiovisual media on the level of knowledge, attitudes, and skills.